The Role of Mobile Learning in Facilitating Science Learning to Enhance Higher Order Thinking Skills (HOTS): A Systematic Review - Ansori, Isa; Arianto, Fajar; Khotimah, Khusnul (Universitas Veteran Bangun Nusantara, 2024)
The existence of mobile devices and technological developments have made mobile-based learning a major trend in education, from elementary to secondary schools in Indonesia. This research is a systematic literature review limited to 10 articles published between 2018 and 2023. The aim of this research is to answer questions about the use of mobile technology in learning contexts as well as the types of learning models used in science teaching to improve students' higher-order thinking abilities. The results of this research are in accordance with the research objectives, where the mobile technology most often used to achieve learning objectives is smartphones and tablets. The most effective learning models in improving high-level thinking skills in science learning are problem based learning, project based learning, Inquiry learning, Collaborative learning, Flipped Classroom, and Blended Learning. The hope is that this research can become a reference for subsequent research in developing creative learning methods.